Analisis Implementasi Program “Kampus Mengajar” Dalam Upaya Peningkatan Minat Belajar & Optimalisasi Nilai Matematika Kelas V SDN Simokerto I / 134 Surabaya - Irgi Putri Olivia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
One of the government programs created to realize MBKM (Free Learning and Independent Campus) activities is the Teaching Campus. This program is intended for students as agents of change to increase human resources by contributing and providing innovation to educational problems, especially in learning activities. This campus teaching activity includes several activities regarding literacy and numeracy, adapting technology to more innovative methods. The Covid-19 pandemic has caused changes in students' learning patterns (Learning Loss), which has had a major impact on children's interest in learning, understanding of the material and learning outcomes. In connection with existing problems, the aim of writing this journal is to have a direct impact on holding campus teaching programs. Research or studies from this journal were carried out using a qualitative approach in the form of collecting data on learning outcomes during the program. The results of research and studies show that there is an increase in students' interest in learning by using learning media that is more exciting and fun. Apart from that, this learning method is very effective in increasing the value of the learning outcomes of class V students at SDN Simokerto I / 134. Good learning outcomes come from good learning methods, because interest in learning is proportional to the understanding gained too.